Pengobatan Malaria Kombinasi Artemisinin (ACT) di Provinsi Papua Barat Tahun 2013 - Revi Rosavika Kinansi; Rika Mayasari; Diana Andriyani Pratamawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Malaria is still a disease with highest incidence rate in Indonesias. Based on Riskesdas 2013, the prevalence of malaria in West Papua was generally increasing. This study aimed to find the correlation of type of malaria found in blood examination and distribution status of ACT. Samples of data obtained by stratified random sampling from 1490 people who had suffered from malaria in West Papua. Data analysis using univariate descriptive and correlation analysis The result showed that the most common type of malaria was tertiana malaria caused by Plasmodium vivax (51%). Early detection performed within the first 24 hours when the patient is suffering from fever can be used as the basis for a policy that early detection can reduce malaria morbidity. It can be concluded ACT suitable for any type of malaria. The concistency of provision of ACT can be implemented by increasing public awareness of taking prophylactic. In addition the ideal combination antimalarial drugs be able to heal in a short time and if the patients performs the compliance of taking the drug, it will not be antimalarial resistance.